B‐cell receptor configuration and adverse cytogenetics are associated with autoimmune hemolytic anemia in chronic lymphocytic leukemia. Issue 1 (31st October 2012) - Maura, Francesco; Visco, Carlo; Falisi, Erika; Reda, Gianluigi; Fabris, Sonia; Agnelli, Luca; Tuana, Giacomo; Lionetti, Marta; Guercini, Nicola; Novella, Elisabetta; Nichele, Ilaria; Montaldi, Anna; et al.
Abstract The development of autoimmune hemolytic anemia (AIHA) in patients with chronic lymphocytic leukemia (CLL) is associated with specific biological features. The occurrence of AIHA was hereby investigated in a retrospective series of 585 CLL patients with available immunoglobulin heavy chain variable (IGHV) gene status. AIHA occurred in 73 patients and was significantly associated with an IGHV unmutated (UM) status (P < 0.0001) and unfavorable [del(17)(p13) and del(11)(q23)] cytogenetic lesions (P < 0.0001). Stereotyped HCDR3 sequences were identified in 29.6% of cases and were similarly represented among patients developing or not AIHA; notably, subset #3 was associated with a significantly higher risk of AIHA than the other patients (P = 0.004). Multivariate analysis showed that UM IGHV, del(17)(p13) and del(11)(q23), but not stereotyped subset #3, were the strongest independent variables associated with AIHA. Based on these findings, we generated a biological risk score for AIHA development according to the presence of none (low risk), one (intermediated risk), or two (high risk) of the independent risk factors. Overall, our data indicate that UM IGHV status and/or unfavorable cytogenetic lesions are associated with the risk of developing secondary AIHA in CLL patients and suggest a possible role of specific stereotyped B‐cell receptor subsets in a proportion of cases. Am. J. Hematol. 2013. © 2012 Wiley Periodicals, Inc.